2020
DOI: 10.1021/acs.chemrestox.0c00156
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to the Heavy-Metal Lead Induces DNA Copy Number Alterations in Zebrafish Cells

Abstract: DNA copy number variants are associated with the development of complex neurological diseases and disorders including autism spectrum disorder, schizophrenia, Alzheimer's disease, and Parkinson's disease. Exposure to multiple environmental chemicals including various heavy metals is suggested as a risk factor in these neurological diseases and disorders, but few studies have addressed if heavy-metal exposure can result in de novo DNA copy number changes as a genetic mechanism contributing to these disease outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Tian et al (2020) found that parental zebrafish exposure to 1 µM Cd for 60 days resulted in malformed offspring and reduced levels of 3,5,3′-triiododenosine (T3) and thyrox-ine (T4), which caused reproductive toxicity and thyroid endocrine system developmental toxicity. Exposure to the heavy metal Pb causes intestinal microbiota imbalance, liver metabolism disorders (Xia et al, 2018), developmental toxicity, and neurotoxicity in zebrafish (Lee & Freeman, 2020). Chen et al (2012) confirmed that the exposure of zebrafish embryos to Pb can cause malformations, change the spontaneous movement and behavior of larvae in a dose-dependent manner, and result in learning and memory deficits in adulthood.…”
Section: Heavy Metalsmentioning
confidence: 77%
See 1 more Smart Citation
“…Tian et al (2020) found that parental zebrafish exposure to 1 µM Cd for 60 days resulted in malformed offspring and reduced levels of 3,5,3′-triiododenosine (T3) and thyrox-ine (T4), which caused reproductive toxicity and thyroid endocrine system developmental toxicity. Exposure to the heavy metal Pb causes intestinal microbiota imbalance, liver metabolism disorders (Xia et al, 2018), developmental toxicity, and neurotoxicity in zebrafish (Lee & Freeman, 2020). Chen et al (2012) confirmed that the exposure of zebrafish embryos to Pb can cause malformations, change the spontaneous movement and behavior of larvae in a dose-dependent manner, and result in learning and memory deficits in adulthood.…”
Section: Heavy Metalsmentioning
confidence: 77%
“…(2020) found that parental zebrafish exposure to 1 µM Cd for 60 days resulted in malformed offspring and reduced levels of 3,5,3′‐triiododenosine (T3) and thyroxine (T4), which caused reproductive toxicity and thyroid endocrine system developmental toxicity. Exposure to the heavy metal Pb causes intestinal microbiota imbalance, liver metabolism disorders (Xia et al., 2018), developmental toxicity, and neurotoxicity in zebrafish (Lee & Freeman, 2020). Chen et al.…”
Section: Research Progress In the Toxicological Assessment Of Hazards...mentioning
confidence: 99%
“…This indicates that aluminuminduced AD is due to increased AChE activity. A recent study assessed the neurotoxic role of lead (Pb), a heavy metal, in zebrafish fibroblast cells (Lee and Freeman, 2020). The findings suggested that Pb exposure results in de novo DNA copy number alterations in a dose-dependent manner.…”
Section: Neurotoxic Zebrafish Models Of Alzheimer's Diseasementioning
confidence: 99%
“…As a non-essential element, lead (Pb) accumulated in soils has become an immense risk for animals and humans due to its toxicity even at low concentrations [3][4][5]. Short-term exposure to Pb can cause brain and kidney damage, while long-term exposure can harm the central nervous and reproductive system, which can even lead to death [6][7][8]. China has the second largest Pb reserves in the world, producing an estimated two million metric tons of Pb in 2021 [9].…”
Section: Introductionmentioning
confidence: 99%